3-5세 유아의 정서어휘 표현에 관한 연구 - 김선희(Sun Hee Kim); 박은실(Eun Sil Park); 신혜정(Hye Jung Shin) (언어치료연구, 2022)
목적: 타인과의 상호작용 속에서 사고와 함께 정서를 표현할 때, 언어적인 의사소통 방식은 더 직접적이고 효과적이라고 할 수 있다. 이러한 정서어휘를 사용하기 위하여 어휘의 의미를 이해하고 상황에 적절하게 표현하는 능력이 요구된다. 본 연구는 연령에 따른 유아들의 정서어휘의 표현능력을 살펴보고, 정서유형에 따른 어휘의 출현 빈도와 백분율을 살펴보는 데 연구의 목적이 있다.방법: 본 연구에 참여한 대상은 3-5세 유아 85명(3세 25명, 4세 30명, 5세 30명)이다. 연구대상 유아들의 정서어휘의 표현능력과 정서유형에 따른 어휘의 출현 빈도와 백분율을 살펴보았으며, 일원변량분석(one-way ANOVA)과, Scheffe 다중범위 검정(Scheffe’s multiple range test)을 통하여 유의한 차이를 검정하였다.결과: 연구결과는 다음과 같다. 첫째, 정서어휘의 표현능력은 연령이 증가할수록 유의미한 차이가 있는 것으로 나타났다. Scheffe 다중범위 검정 결과, 정서어휘의 표현능력은 3세, 4세, 5세 사이에서 유의미한 차이가 있는 것으로 나타났다. 둘째, 정서유형에 따른 어휘의 출현 빈도와 백분율을 분석한 결과, 3세보다는 4, 5세 유아들이 좀 더 다양한 정서어휘를 표현하는 것으로 나타났으며, 어휘의 전체 출현 빈도는 연령이 증가할수록 높았다. 정서유형에 따른 어휘의 출현 빈도를 살펴본 결과 ‘기쁨’군의 표현 빈도가 가장 높게 나타났으며, 그 다음으로 ‘슬픔, 두려움, 노여움’군 순으로 나타났다.결론: 본 연구의 함의는 정서표현에 어려움을 가진 아동들의 정서어휘 지도 시 목표어휘를 선정하는 데 기초 자료로 제시될 수 있을 것이다. Purpose: When expressing emotions with thoughts in interactions with others, verbal communication methods are more direct and effective. In order to use emotional vocabulary, the ability to understand the meaning of the vocabulary and express it appropriately for the situation is required. The purpose of this study is to examine the expression ability of infants' emotional vocabulary, and to examine the frequency and percentage of vocabulary appearance according to emotion types. Methods: The subjects of this study included 85 children aged between three and five years of age. The frequency and percentage of vocabulary appearance according to emotional vocabulary and emotional type were examined. Significant differences were tested through one-way ANOVA and Scheffé multiple range test. Results: The results of this study are as follows. First, it was found that there was a significant difference in emotional vocabulary expression ability with increasing age. As a result of the Scheffé multiple range test, there was a significant difference in the expressive ability of emotional vocabulary among thee-, four-, and five-year-old subjects. Second, as a result of analyzing the appearance frequency and percentage of vocabulary according to emotion type, it was found that four- and five-year-old subjects expressed more diverse emotional vocabulary than three-year-old subjects. In addition, the overall frequency of appearance of the expression vocabulary increased as age increased. As a result of examining the frequency of appearance of vocabulary according to emotion type, the expression frequency of 'joy' was found to be the highest, followed by 'sadness,' 'fear,' and 'anger,' respectively. Conclusions: The implications of this study can be presented as basic data for selecting emotional vocabulary for children with disabilities in emotional expression. KCI Citation Count: 0